2008
DOI: 10.1002/ejlt.200700307
|View full text |Cite
|
Sign up to set email alerts
|

The effect of malaxation temperature on the virgin olive oil phenolic profile under laboratory‐scale conditions

Abstract: The relationship between olive paste malaxation temperature and the concentration of olive oil hydrophilic phenols (HP), i.e. simple phenols, secoiridoids and lignans, was investigated. Malaxation experiments were performed at laboratory scale for 45 min at 21, 24, 27, 30, 33 and 36 7C. A significant (p ,0.05) increment of total phenols concentration was found with a maximum at 27 7C, whereas for higher temperatures (30-36 7C) a progressive decrement was observed. A similar pattern was recorded approximately f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 30 publications
2
46
2
Order By: Relevance
“…Kalua et al (2006) and Kalua et al (2007) reported compatible results in their two different studies where no significant change in phenolic content of olive oil sample was observed with changing temperature and time of malaxation step. Moreover adverse effect of temperature on total phenolic content was also reported by Parenti et al (2008) in which temperature higher than 27°C adversely affected the transition of phenolics to olive oil.…”
Section: Resultsmentioning
confidence: 98%
“…Kalua et al (2006) and Kalua et al (2007) reported compatible results in their two different studies where no significant change in phenolic content of olive oil sample was observed with changing temperature and time of malaxation step. Moreover adverse effect of temperature on total phenolic content was also reported by Parenti et al (2008) in which temperature higher than 27°C adversely affected the transition of phenolics to olive oil.…”
Section: Resultsmentioning
confidence: 98%
“…It is likely that the lower temperature delayed the hydrolytic and oxidative degradation of phenolic compounds in the amurca extract. It has been reported that the total phenolic content of olive oil was increased in cold pressed olives (Parenti et al, 2008). Also, oil that was obtained from olives stored at 5 to 10 °C experienced lower hydrolytic, oxidative degradation and off-odour development (Clodoveo et al, 2007;Inarejos-García et al, 2010).…”
Section: Drganismmentioning
confidence: 97%
“…All of these operations can affect the quality, chemical composition and sensory characteristics of the final product, and therefore optimisation of these extraction steps is necessary (Kiritsakis, 1998). The malaxing process has been widely investigated and several works have reported the effect of the malaxation variables: temperature (Parenti, Spugnoli, Masella, & Calamai, 2008;Ranalli, Contento, Schiavone, & Simone, 2001), time (Di Giovacchino, Costantini, Ferrante, & Serraiocco, 2002;Ranalli, Pollastri, Contento, Iannucci, & Lucera, 2003) and even both (Gó mez-Rico, Inarejos-Garci´a, Salvador, & Fregapane, 2009;Jimé-nez, Hermoso, & Uceda, 1995;Kalua, Bedgoog, Bishop, & Prenzler, 2006) on the composition and quality of virgin olive oil. The influence of the separation process has also been largely described (Salvador, Aranda, Gómez-Alonso, & Fregapane, 2003;Torres & Maestri, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to our knowledge, there is little data on the effect of the crushing level although its regulation is essential for obtaining good process yields (Uceda, Jiménez, & Beltrán, 2006) and may have significant influence on the transfer of components to the oil . On the other hand, most of the olive oil processing studies are mainly focussing on volatile and phenolic compounds (Gó mez-Rico et al, 2009;Kalua et al, 2006;Parenti et al, 2008), hence neglecting other minor compounds like pigments, sterols, squalene, and triterpenes amongst others.…”
Section: Introductionmentioning
confidence: 99%